Migration and land rental as responses to income shocks in rural China - Ward, Patrick S.; Shively, Gerald E. (Wiley, 2015)
Using longitudinal household survey data from rural China and an identification strategy based on observed rainfall realizations, we are able to test household responses to idiosyncratic and covariate income shocks. We find that negative idiosyncratic income shocks increase migration and elicit household out rental of land. The effect of covariate income shocks is generally dependent on both the timing and the nature of the shock. Our results suggest that rainfall deficiencies during paddy maturing or harvesting seasons reduce the number of migrants by raising the marginal value product of farm labour, thereby increasing the opportunity costs associated with migration.